Membangun Moralitas Pada Anak Usia Dini Melalui Metode Bermain - Cantika Putri; Fitri Febri Handayani; Naili Rohmah (JIEEC (Journal of Islamic Education for Early Childhood)., 2025)
Moral education in early childhood is a crucial foundation in character building. The main objective of this study is to analyze the effectiveness of storytelling in developing morality among young children. This study employs a literature review as the primary method by analyzing national and international sources from the last ten years. The findings reveal that storytelling is effective in instilling moral values such as empathy, honesty, responsibility, and respect, especially when supported by appropriate media such as puppets, folktales, or interactive digital platforms. The internalization of moral values occurs through children's emotional engagement with the story and its characters. The study concludes that storytelling is a strategic approach in early childhood character education and has the potential to be integrated into culturally and technologically-based learning curricula.